Correction to: Guiding principles on the education and practice of theranostics. - Pascual, Thomas N. B.; Paez, Diana; Iagaru, Andrei; Gnanasegaran, Gopi; Lee, Sze Ting; Sathekge, Mike; Buatti, John M.; Giammarile, Francesco; Al‑Ibraheem, Akram; Pardo, Manuela Arevalo; Baum, Richard P.; De Bari, Berardino; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
The article addresses a correction to a previously published work in the European Journal of Nuclear Medicine and Molecular Imaging, specifically acknowledging the omission of Dr. Jolanta Kunikowska from the author list. Dr. Kunikowska is affiliated with the Nuclear Medicine Department at the Medical University of Warsaw, Poland. This erratum ensures that her contribution is recognized in the corrected version of the article. The publisher, Springer Nature, maintains a neutral stance regarding jurisdictional claims in published maps and institutional affiliations.